Frontiers in Multiscale Modeling of Photoreceptor Proteins. (13th February 2021) - Mroginski, Maria‐Andrea; Adam, Suliman; Amoyal, Gil S.; Barnoy, Avishai; Bondar, Ana‐Nicoleta; Borin, Veniamin A.; Church, Jonathan R.; Domratcheva, Tatiana; Ensing, Bernd; Fanelli, Francesca; Ferré, Nicolas; Filiba, Ofer; et al.
Abstract: This perspective article highlights the challenges in the theoretical description of photoreceptor proteins using multiscale modeling, as discussed at the CECAM workshop in Tel Aviv, Israel. The participants have identified grand challenges and discussed the development of new tools to address them. Recent progress in understanding representative proteins such as green fluorescent protein, photoactive yellow protein, phytochrome, and rhodopsin is presented, along with methodological developments. Abstract : This perspective article highlights the challenges in the theoretical description of photoreceptor proteins using multiscale modeling, as discussed at the CECAM workshop in Tel Aviv, Israel. The participants have identified grand challenges and discussed the development of new tools to address them. Recent progress in understanding representative proteins such as green fluorescent protein, photoactive yellow protein, phytochrome, and rhodopsin is presented, along with methodological developments.